Ninety-day and one-year healthcare utilization and costs after knee arthroplasty. Issue 10 (October 2019) - Hung, A.; Li, Y.; Keefe, F.J.; Ang, D.C.; Slover, J.; Perera, R.A.; Dumenci, L.; Reed, S.D.; Riddle, D.L.
Summary: Objectives: This study examined ninety-day and one-year postoperative healthcare utilization and costs following total knee arthroplasty (TKA) from the health sector and patient perspectives. Design: This study relied on: 1) patient-reported medical resource utilization data from diaries in the Knee Arthroplasty Pain Coping Skills Training (KASTPain) trial; and 2) Medicare fee schedules. Medicare payments, patient cost-sharing, and patient time costs were estimated. Generalized linear mixed models were used to identify baseline predictors of costs. Results: In the first ninety days following TKA, patients had an average of 29.7 outpatient visits and 6% were hospitalized. Mean total costs during this period summed to 3, 720, the majority attributed to outpatient visit costs (84%). Over the year following TKA, patients had an average of 48.9 outpatient visits, including 33.2 for physical therapy. About a quarter (24%) of patients were hospitalized. Medical costs were incurred at a decreasing rate, from 2, 428 in the first six weeks to 648 in the last six weeks. Mean total medical costs across all patients over the year were 8, 930, including 5, 328 in outpatient costs. Total costs were positively associated with baseline Charlson comorbidity score ( P < 0.01). Outpatient costs were positively associated with baseline Charlson comorbidity score ( P = 0.03) and a bodily pain burden summary score ( P < 0.01). Mean patient cost-sharing summed to 1, 342 and time costs summed to 1, 346. Conclusions: Costs in the ninety days and year after TKA can be substantial for both healthcare payers and patients. These costs should be considered as payers continue to explore alternative payment models.